Pengenalan Olahraga Workout pada Siswa MTS Al-Falah Fi’lial Pulubala Kabupaten Gorontalo - Zulkifli A. Lamusu (Institut Nalanda, 2024)
This community service activity aims to introduce exercise sports as an effort to improve physical fitness in MTs Al-Falah Fi'lial Pulubala students, Gorontalo Regency. Given the importance of physical fitness for adolescents in supporting growth and development, this program is designed to provide an understanding of workout sports that are flexible, easy to implement, and beneficial to health. The program uses lectures, questions and answers, and demonstrations to convey information about the benefits of workout sports, basic movement techniques, and the importance of body fitness. The activity was attended by 20 students aged 13-14 years, with the results of the evaluation showing that 85% of the students succeeded in understanding the material presented. In addition to improving physical fitness, exercise sports also have a positive impact on students' mental health, such as reducing stress and increasing study concentration. It is hoped that this program can build healthy living habits among teenagers and become a model for useful community service activities in the future.